CALCULATION OF EFFORTS OF DIGGING BY THE WORKING EQUIPMENT OF THE BULLDOZER - A. I. Demidenko; K. Yu. Gatych (Вестник СибАДИ, 2017)
In the work a new design of the working equipment of the bulldozer is considered, which makes it possible to increase productivity, by capturing and transporting an extra blade of two pile at once. In this connection, it was necessary to compile a design scheme for determining the resistance to digging an extra blade. Was received the graph of the force dependence on the rod of the hydraulic cylinder from the stroke of the rod, when digging an additional blade.